2017
DOI: 10.5301/uj.5000269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Waves Emitted from 3G+Wi-Fi Modems on Human Semen Analysis

Abstract: Objective: The purpose of this study was to evaluate the effects of 3G+wifi modems on human sperm quality. A total of 40 semen specimens were gathered between March and September 2015, from healthy adult men. Methods: The sperm samples were divided into two groups - 3G+wi-fi exposed and unexposed groups. In the unexposed group, the specimens were shielded by aluminum foil in three layers and put into an incubator at a temperature of 37°C for 50 minutes. The exposed group was positioned in another room in an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Although studies have shown that better sperm quantity among men attending a fertility clinic is usually correlated with wearing boxer-style underwear (30,31), improvement in time-to-pregnancy remains to be established (32). The adverse effects of using mobile cell phones, laptop computers, and Wi-Fi on sperm parameters have mainly been studied (33)(34)(35)(36)(37)(38)(39) in animals, in vitro, or among small numbers of men with very short-term observational data that did not measure reproductive outcomes. We are in need of good evidence to demonstrate long-term negative affects of electromagnetic waves and to support the efficacy of reducing their exposure for improving the relevant reproductive outcomes.…”
Section: Con 3 Mark Sigman MD Lifestyle Changesmentioning
confidence: 99%
“…Although studies have shown that better sperm quantity among men attending a fertility clinic is usually correlated with wearing boxer-style underwear (30,31), improvement in time-to-pregnancy remains to be established (32). The adverse effects of using mobile cell phones, laptop computers, and Wi-Fi on sperm parameters have mainly been studied (33)(34)(35)(36)(37)(38)(39) in animals, in vitro, or among small numbers of men with very short-term observational data that did not measure reproductive outcomes. We are in need of good evidence to demonstrate long-term negative affects of electromagnetic waves and to support the efficacy of reducing their exposure for improving the relevant reproductive outcomes.…”
Section: Con 3 Mark Sigman MD Lifestyle Changesmentioning
confidence: 99%
“…Exposure did not affect overall sperm viability, but exposure to laptop RF-EMR did result in significant reductions in sperm motility [progressive sperm motility 68.7%±8.8% (treatment) vs. 80.9%±7.5% (control), P<0.01; immotile sperm 24.5%±7.6% (treatment) vs. 13.6%±5.6% (control), P<0.01] and increases in DNA fragmentation assessed on TUNEL assay [8.6%±6.6% (treatment) vs. 3.3%±6.0% (control), P<0.01]. Other studies have also supported a negative impact on sperm motility following exposure to laptop activity with 3G wireless internet transmission (76).…”
Section: Radiationmentioning
confidence: 89%
“…This result is in accord with other researches, amounts of industrial chemicals will do harm to reproductive system and reduce semen quality. 13,23 There are few works had analyzed the relationship between computer using and semen quality, but related factors (sitting for a long time, 24 electromagnetic wave 25 and radiation, 26 et al) had been reported to be related to lower semen quality. To gure out the mechanisms of such multi-angle effects factors are quite challenging but also essential job, especially in the current condition when computers are widely used.…”
Section: Discussionmentioning
confidence: 99%